P134/O32 Selective expansion of a thymic-derived and functionally competent regulatory T cell population by low-dose IL-2 therapy in patients with refractory SLE. (March 2019) - Humrich, JY; von Spee-Mayer, C; Siegert, E; Bertolo, M; Rose, A; Abdirama, D; Enghard, P; Stuhlmüller, B; Hiepe, F; Alexander, T; Feist, E; Radbruch, A; et al.
Abstract : Career situation of first and presenting author: Instructor. Objectives: An acquired deficiency of interleukin-2 (IL-2) and related defects in regulatory T cell (Treg) homeostasis play a crucial role in the pathogenesis of SLE. Here, we report the responses of Treg and other lymphocyte subsets to low-dose IL-2 therapy observed during an open-label, uncontrolled, dose adaption, phase 1/2a single-center clinical trial in patients with active and refractory SLE. Methods: 12 patients with active and refractory SLE (SLEDAI ≥6) were treated at our site with a low-dose IL-2 regimen consisting of four separate treatment cycles each with daily subcutaneous injections of recombinant human IL-2 (aldesleukin) at single daily doses of either 0.75, 1.5 or 3.0 million IU for five consecutive days. Cells from peripheral blood were analyzed by flow cytometry before and one day after each treatment cycle. Results: All patients showed highly significant cycle- and dose-dependent increases in the proportions and absolute numbers of CD3+CD4+FoxP3+CD127 lo Treg and of CD25hi expressing cells among Treg. By contrast, we observed no relevant changes in the absolute numbers of CD3+CD4+FoxP3 conventional T cells (Tcon), of CD3+CD8+ T cells, of CD3+CD56+NK T cells and of CD3-CD56+NK cells. The IL-2 expanded Treg population displayed a preserved suppressive capacity and expressed high levels of the Treg-associated molecules Helios, CD39 and CD137. In addition, we noted robust and dose-dependent increases in the proportions of Treg expressing the proliferation marker Ki67. Although significant increases in the proportions of Ki67 +cells among Tcon and also among other lymphocyte subsets were observed at the end of each treatment cycle, the calculated ratio between Ki67+ Treg and Ki67+ Tcon continuously increased and was significantly higher at the end of the treatment phase, suggesting a preferential targeting of the Treg population. Conclusions: Low-dose IL-2 therapy promotes the selective expansion of a functionally competent and thymic-derived Treg population in patients with refractory SLE. This study also provides novel insights into the pharmacodynamics and the broad biologic effects of low-dose IL-2 therapy. Disclosure of Interest: J. Humrich Consultant for: ILTOO Pharma, C. von Spee-Mayer: None declared, E. Siegert: None declared, M. Bertolo: None declared, A. Rose: None declared, D. Abdirama: None declared, P. Enghard: None declared, B. Stuhlmüller: None declared, F. Hiepe: None declared, T. Alexander: None declared, E. Feist: None declared, A. Radbruch: None declared, G.-R. Burmester: None declared, G. Riemekasten Consultant for: ILTOO Pharma.